Hazard Detection among Young and Experienced Drivers via Driving Simulator - Borhan, N.; Ibrahim, M.K.A.; Ab Rashid, A.A. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Hazard perception test (HPT) is one of a common task in perceiving hazard among drivers. Many countries have been adopting this method to assess an individual’s driving competency in order to acquire driving licenses. Computer-based assessment was a common method widely used to carry out the HPT. Previous hazard perception studies using Malaysian samples reported mixed findings on the effectivity of reaction time-based HPT. Dissimilar with the common method, this study employed a full-size cabin driving simulator to study hazard perception, focussing on hazards detection between two groups of drivers: young and experienced. Results from 28 (15 young, 13 experienced) drivers indicated that young drivers detected hazards faster than their experienced counterparts, even though both groups have the same performance of hazard recognition. Correlational analysis revealed that driving frequency may be a factor contributing to the difference in response time between these two groups. Further analysis also indicates that different road environments contribute to different hazard perception performance.